PENGEMBANGAN INSTRUMEN PENGUKURAN LITERASI MATEMATIKA PADAMATERI ARITMATIKA SOSIAL BERBASIS PENDEKATAN KONTEKSTUAL - Fauziah, Qoriatun; Zainudin, M; Nurdianingsih, Fitri (IKIP PGRI Bojonegoro, 2022)
This research is a development research that aims to produce an instrument for measuring mathematical literacy by looking at the procedures and analyzing the quality of the instrument developed. This type of research is research and development which consists of 4 stages, namely: (1) preliminary stage, (2) self-evaluation stage, (3) prototyping stage and (4) field test stage. In this validation, the measurement instrument is declared valid with a validity coefficient of 0.68 which is in the range of 0.4 < V 0.8. The results of the empirical validation test meet the valid criteria for all items. The results of the reliability test by students obtained a total score of 0.80. This value indicates that the reliability of the measurement instrument in the very high category means that it is reliable. The results of the test of the level of difficulty by students obtained an average score of 0.52. This value indicates that the level of difficulty of the measurement instrument is in the medium category. The results of the test of discriminating power by students obtained a final score of 0.32. This value indicates that the level of discriminating power of the measurement instrument is in the good category. The results of the practicality level trial by students obtained a score of 81.15%. This value indicates that the level of practicality of the measurement instrument is in the positive category. The results of the effectiveness test obtained a percentage of 66.67% with a good category.Keywords:Measurement Instrument; Mathematic Literacy; Contextual Approach